Pengembangan Modul Ajar Fisika Berbasis Alur Merdeka untuk Meningkatkan Hasil Belajar Fisika di MAN 1 Buton Selatan - Nursyahitna; Helmi; Kaharuddin Arafah (Jurnal Penelitian Pendidikan IPA, 2024)
This research is a type of Research and Development (R&D) study utilizing the 4D model development method (Define, Design, Development, and Dissemination). The study was conducted at MAN 1 Buton Selatan with the aim of designing and analyzing a valid, practical, and effective Merdeka flow-based physics teaching module that can improve student learning outcomes. The developed Merdeka flow-based physics teaching module was then tested on 25 students of class X-1 and evaluated by 10 practitioners or physics teachers from Siompu District and West Siompu District, Buton Selatan. The instruments used in this study included a validation sheet for the physics teaching module, practitioner assessment questionnaires, and a validated student learning outcomes test. The results showed that the Merdeka flow-based physics teaching module at MAN 1 Buton Selatan was valid, with an Aiken's V value of 0.74, practical, with a practitioner response score of 92.44%, and effective, with 80% of students showing a high category improvement in physics learning outcomes based on the N-gain calculation. Based on the results, the Merdeka Flow-based physics teaching module is overall considered valid, practical, and effective for use in the physics learning process.